Growth, single-crystal structure, and magnetic properties of the double molybdate KYb(MoO4)2. (July 2021) - Armand, P.; Reibel, C.; Granier, D.; Tillard, M.
Abstract: Crystals of the rare earth double molybdate KYb(MoO4 )2 were grown by spontaneous nucleation from a K2 Mo4 O13 flux. The typical crystals were colorless and elongated, well-developed plates. The material has been characterized by powder X-ray diffraction (PXRD), energy-dispersive X-ray spectrometry (EDS), and Raman spectroscopy methods. The structural properties have been investigated through single-crystal X-ray diffraction at room temperature. KYb(MoO4 )2 crystallizes in the orthorhombic symmetry, space group Pbcn (No. 60), a = 5.0395(2), b = 18.2821(9), c = 7.8635(4) Å, and Z = 4. A complete ordering of the Yb 3+ and Mo 6+ cations has been found. The Yb 3+ ions are located in distorted YbO8 antiprisms which form chains of edge-sharing, aligned along the c -axis while the Mo 6+ ions are placed in a slightly deformed tetrahedral environment of oxygen atoms. Double bridge modes of the "Mo2 O8 dimers" have been identified in the unpolarized Raman spectra. The temperature-dependent magnetic susceptibility of KYb(MoO4 )2 follows a Curie–Weiss law with a Weiss constant of −52 K. Highlights: Flux-growth of millimeter size, colorless, and transparent KYb(MoO4 )2 single crystals. KYb(MoO4 )2 crystallizes in the orthorhombic symmetry, space group Pbcn (No. 60). Ordered distribution of the K + and Yb 3+ cations on C 2 symmetry positions. Existence of "Mo2 O8 dimers" confirmed by the Raman band at 736 cm −1 . Large Weiss constant value of θ p = −52 K.